2009
DOI: 10.1136/ard.2008.096677
|View full text |Cite
|
Sign up to set email alerts
|

EULAR recommendations for the treatment of systemic sclerosis: a report from the EULAR Scleroderma Trials and Research group (EUSTAR)

Abstract: Purpose: The optimal treatment of systemic sclerosis (SSc) is a challenge because the pathogenesis of SSc is unclear and it is an uncommon and clinically heterogeneous disease affecting multiple organ systems. The aim of the European League Against Rheumatism (EULAR) Scleroderma Trials and Research group (EUSTAR) was to develop evidence-based, consensus-derived recommendations for the treatment of SSc. Methods: To obtain and maintain a high level of intrinsic quality and comparability of this approach, EULAR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
327
0
36

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(366 citation statements)
references
References 76 publications
3
327
0
36
Order By: Relevance
“…Histological examination showed thinning of the collagen fiber bundles in the dermis. Since there are few therapeutic drugs for SSc at the present time [116], these improvements observed in two SSc patients suggest that tocilizumab appears to be a promising biologic for the treatment of SSc.…”
Section: Systemic Sclerosismentioning
confidence: 94%
“…Histological examination showed thinning of the collagen fiber bundles in the dermis. Since there are few therapeutic drugs for SSc at the present time [116], these improvements observed in two SSc patients suggest that tocilizumab appears to be a promising biologic for the treatment of SSc.…”
Section: Systemic Sclerosismentioning
confidence: 94%
“…Suda et al (2009) suggested that advanced age was a risk factor for acute exacerbation in connective tissue disease-related ILD, but the age of onset was not an associated factor in our study (Table 4). About 10%-20% of patients with SSc had overlapping features with other rheumatic diseases (Kowal-Bielecka et al 2009;Pakozdi et al 2011). Pakozdi et al (2011) reported that the most common connective tissue disease was PM/DM, followed by rheumatoid arthritis and Sjögren's syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Nonpharmacologic care can target a broad range of symptoms simultaneously, depending on the needs expressed by patients. To help guide medical care for patients with SSc, the European League Against Rheumatism (EULAR) and the EULAR Scleroderma Trials and Research group have developed evidence-based, consensus-derived recommendations for the pharmacologic treatment of SSc (12). The authors of these guidelines also emphasized the potential importance of psychosocial and rehabilitation interventions in disease management but could not make recommendations for or against these types of interventions.…”
Section: Introductionmentioning
confidence: 99%